The evolution of intractable Ménière’s disease: attacks resolve over time - Gerritsen, F. R.; Schenck, A. A.; Locher, H.; van de Berg, R.; van Benthem, P. P.; Blom, H. M. (Frontiers in Neurology, 2024)
Introduction Knowledge of the natural and temporal course of a disease is important when deciding if an intervention is appropriate. In the case of Ménière’s disease (MD), there is some evidence that attacks diminish over time, but the topic remains controversial. A conservative approach to surgery is usually followed in northern Europe, and leads to strict patient selection before considering surgery. Here, we describe the evolution of vertigo attacks among a group of intractable MD patients in whom surgery was considered. Methods Retrospective cohort study in a Ménière’s disease expert center. Patients with definite unilateral Ménière’s disease and persisting vertigo attacks despite treatment with intratympanic steroid injections were included. All patients had been waitlisted for participation in a planned trial assessing non-ablative surgery. They were waitlisted between June 2016 and June 2021 without undergoing the surgical intervention. In September 2022, data were collected from patient’s files and follow-up telephone interviews were conducted to assess the evolution of their vertigo attacks. Results Thirty-five patients (54% male, mean age of onset 52 years, 51% right sided) were included in the analysis. Twenty-five patients (71%) eventually declined surgery. Of the 33 patients with complete information on vertigo attacks, 21 (64%) were free of vertigo attacks upon data collection, after a median disease duration of 5.3 years. Patients who did undergo surgery, had longer duration of disease than patients who did not. Discussion Even in a population with intractable MD, most patients will experience relief of symptoms over time. On one hand, active treatment may accelerate relief of symptoms, but on the other hand, non-ablative therapies are of debatable effect and ablative intervention carries a risk of life long side effects. Therefore, any active intervention should be carefully considered.